Manajemen Strategi Dakwah Walisongo di Wilayah Pulau Jawa - Ibdalsyah; Ramly, Amir Tengku; Rosyadi, Rahmat (Jurnal Manajemen, 2023)
The success of the spread of Islam on the island of Java shows that the Walisongo have good missionary management. Evidence in the form of facts, data and information in this research can be traced from historical sites by confirming to the guards and security passed down from generation to generation from the direct heirs and officials in the local area. In addition, various documents in the form of literature can be studied in depth. This research was conducted using a case study approach related to managing the Walisongo da'wah strategy in the region of Java Island. The data used comes from literature and documents, with data analysis carried out in a descriptive-normative manner. The results of the study can be concluded that (1) the management of the walisongo's da'wah when they entered Java was carried out with good collaboration and teamwork, (2) the management of the walisongo's da'wah involved people who had positions, both in government and society, (3 ) the management of the walisongo's da'wah uses means through the culture, arts and traditions of the local community, (4) the management of the walisongo's da'wah is practised through educational activities with strategic management principles, which focus on the future with an activity approach and the culture of the community at that time.